Design and Evaluation of a Simplified Rolling Mill with Simple Drive Mechanism - Orhorhoro, Ejiroghene; Chughiefe, Lucky; Ebunilo, Patrick Okechukwu; Tamuno, Rogers Ibunemisam (Journal of Advanced Industrial Technology and Application, 2024)
Rolling milling have become a potential paradigm for changing the inherent workability and microstructural evolution of materials. A rolling mill design is a difficult undertaking that calls for both a solid process understanding and the capacity to make sound decisions in order to balance a number of competing objectives. A medium rolling mill in this research is built to satisfy particular metallurgical specifications for the goods being worked on. Consequently, the design takes into account the machine's rolling force, rolling speed, torque, and power needs. To evaluate the performance of the designed rolling mill, test evaluations were conducted using an Al-6061 alloy with width and thickness of 500 mm and 95 mm, respectively. It was found that the medium rolling mill torque and force were 1670.22 Nm and 422536.98 N. Furthermore, a rolling power of 7 hp and a solid roll shaft diameter of 80 mm were determined. After rolling, the final thickness was between 102.11 and 102.13 mm. Likewise, the actual draft varied from 7.11 to 7.13 mm. Also, 500 mm, 7.118 mm, 88.975%, 95 mm, and 102.118 mm, respectively, are the average width, average actual draft, average efficiency, average original thickness, and average final thickness of Al-6061 alloy. The Al-6061 alloy's final thickness of 102.118 mm and its obtained efficiency of 88.975% show how well the medium rolling mill performs.